Integrated Plant Nutrition System Modules for Major Crops and Cropping Systems in South Asia - Gyeltshen, Kinzang; Sharma, Sheetal (SAARC Agriculture Centre, 2019)
This book ‘Integrated Plant Nutrition System Modules for Major Crops and Cropping Systems in South Asia’ contains the papers and proceedings of the regional expert consultation meeting on Developing Country Specific Integrated Plant Nutrition System Modules for Major Crops and Cropping Systems in South Asia organized at Oak Ray Regency Hotel, Kandy, Sri Lanka from 21-23 August, 2019, jointly by the SAARC Agriculture Centre (SAC), Horticultural Crop Research and Development Institute (HORDI), Department of Agriculture, Government of Sri Lanka and International Rice Research Institute, New Delhi, India. The experts for country papers presentation were the representative of their respective governments. Other experts invited for technical paper presentation were spoken in their personal capacity. The opinions expressed in this publication are those of the authors and do not imply any opinion whatsoever on the part of SAC, especially concerning the legal status of any country, territory, city or area or its authorities, or concerning the delimitation of its frontiers or boundaries.